2003
DOI: 10.1021/om030118z
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate Phosphinoalkoxides:  Synthesis, Deprotonation, and Building Blocks in Polylithium Mixed-Anion Aggregates

Abstract: The bis((dimethylphosphino)methyl)-substituted alcohol (Me 2 PCH 2 ) 2 CHOH (1) was prepared from the respective bis(3,5-dimethylbenzyl)phosphonium dichloride by reductive elimination of mesitylene with lithium alanate in 56% yield. Deprotonation with nbutyllithium or elemental sodium gave the respective alkali metal alcoholates [(Me 2 PCH 2 ) 2 -CHOM] 6 (M ) Li (2), Na (3)). Both compounds have a core consisting of two stacked M 3 O 3 hexagons held together by short M-O bonds. In 2, in addition to three oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…A variable-temperature 31 P{ 1 H} NMR study in toluene- d 8 at −80 °C revealed two distinct 1:1:1:1 quartet resonances at −23.3 and −30.1 ppm with coupling constants of 41 and 60 Hz, respectively, indicating the coordination of the soft phosphorus donors to hard, quadrupolar 7 Li atoms ( I = 3/2, natural abundance 92.6%). The magnitude of these coupling constants is similar to those found for other lithium phosphine complexes such as Li[N( o -C 6 H 4 PPh 2 ) 2 ](THF) 2 (34 Hz), , [Li(THF) 2 ][ o -(2,6-Me 2 C 6 H 3 N)C 6 H 4 PPh 2 ] (34 Hz), [Li(THF) 2 ][ o -(2,6- i Pr 2 C 6 H 3 N)C 6 H 4 PPh 2 ] (38 Hz), [(2,4,6-Me 3 C 6 H 2 )NLi-2-(4-MeC 6 H 3 )] 2 PPh(dioxane) (40 Hz), Li[N( o -C 6 H 4 P i Pr 2 ) 2 ](THF) (46 Hz), Li[N( o -C 6 H 4 PCy 2 ) 2 ](THF) (48 Hz), [(Me 2 PCH 2 ) 3 CO]Li 3 [C(CH P Me 2 ) 3 ] (58 Hz), and the lithium phosphide derivative [Li(tmeda)] 2 [1,2-C 6 H 4 (PPh) 2 ] (35 Hz) . Consistently, the 7 Li{ 1 H} NMR spectrum at −80 °C exhibits two doublet (3.0 ppm, 1 J PLi = 60 Hz; 1.6 ppm, 1 J PLi = 41 Hz) and two singlet (−0.8 and −0.9 ppm) resonances, confirming the phosphorus donor in each dinuclear unit is bound to one rather than two lithium centers.…”
Section: Resultssupporting
confidence: 76%
“…A variable-temperature 31 P{ 1 H} NMR study in toluene- d 8 at −80 °C revealed two distinct 1:1:1:1 quartet resonances at −23.3 and −30.1 ppm with coupling constants of 41 and 60 Hz, respectively, indicating the coordination of the soft phosphorus donors to hard, quadrupolar 7 Li atoms ( I = 3/2, natural abundance 92.6%). The magnitude of these coupling constants is similar to those found for other lithium phosphine complexes such as Li[N( o -C 6 H 4 PPh 2 ) 2 ](THF) 2 (34 Hz), , [Li(THF) 2 ][ o -(2,6-Me 2 C 6 H 3 N)C 6 H 4 PPh 2 ] (34 Hz), [Li(THF) 2 ][ o -(2,6- i Pr 2 C 6 H 3 N)C 6 H 4 PPh 2 ] (38 Hz), [(2,4,6-Me 3 C 6 H 2 )NLi-2-(4-MeC 6 H 3 )] 2 PPh(dioxane) (40 Hz), Li[N( o -C 6 H 4 P i Pr 2 ) 2 ](THF) (46 Hz), Li[N( o -C 6 H 4 PCy 2 ) 2 ](THF) (48 Hz), [(Me 2 PCH 2 ) 3 CO]Li 3 [C(CH P Me 2 ) 3 ] (58 Hz), and the lithium phosphide derivative [Li(tmeda)] 2 [1,2-C 6 H 4 (PPh) 2 ] (35 Hz) . Consistently, the 7 Li{ 1 H} NMR spectrum at −80 °C exhibits two doublet (3.0 ppm, 1 J PLi = 60 Hz; 1.6 ppm, 1 J PLi = 41 Hz) and two singlet (−0.8 and −0.9 ppm) resonances, confirming the phosphorus donor in each dinuclear unit is bound to one rather than two lithium centers.…”
Section: Resultssupporting
confidence: 76%
“…The K-N distance of 2.862(3) A ˚is typical for such a contact; the corresponding distances in 5 range from 2.8008(16) to 2.8725(17) A ˚. As was observed for compounds 3-10, the carbanion centres in 12 and 13 are essentially planar [sum of angles at C(1) = 358.7 (12), 358.0 • (13); displacement of C(1) from the PSi 2 plane towards Na/K: 0.118 (12), 0.148 (13) A ˚]. For comparison, the sum of angles within the CSi 2 P skeletons in [[(Me 3 Si) 2 {Me 2 P(BH 3 )}C]Na(THF) 2 .1/2PhMe] • (16) and [[(Me 3 Si) 2 {Me 2 P(BH 3 )C}K] • (17), 14 which contain genuine M-C carbanion contacts, are 346.3 and 353.5/348.7 • , respectively, with corresponding displacement of the carbanion centre from the Si 2 P plane of 0.199 A ˚(16) and 0.267/0.355 A ˚ (17).…”
Section: Resultsmentioning
confidence: 76%
“…The reaction of [RuCl 2 (PPh 3 ) 3 ] with PhPOO in methanol resulted in the formation of trans-[Ru II Cl 2 (PhP(OMe) 2 ) 2 ] (3). This complex is soluble in dichloromethane, sparingly soluble in acetonitrile and insoluble in most other solvents including diethyl ether and dimethyl sulfoxide.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] As part of our investigation of mixed P,Sdonor ligands [4][5][6] we have been exploring the chemistry of [2-(1,3-dioxolan-2-yl)phenyl]diphenylphosphane (1,PhPOO), [7] and [2-(1,3-dithiolan-2-yl)phenyl]diphenylphosphane (2, PhPSS) (Scheme 1). As well as possessing an enantiotopic carbon centre, these ligands have several possible binding modes, and have the potential to show hemilabile and fluxional behaviour.…”
Section: Introductionmentioning
confidence: 99%